(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2005)
2015 was the deadline by which world leaders pledged to reduce hunger and extreme poverty by half and to make substantial gains in education, health, social equity, environmental sustainability and international solidarity. This study examines progress towards the World Food Summit goals and the Millennium Development Goals (MDGs), focusing on the critical importance of reducing hunger, not only as the explicit target of MDG 1 but as an essential condition for reaching the other MDGs. Hunger and malnutrition are major causes of the deprivation and suffering targeted by all of the other MDGs. Progress towards those targets has lagged, particularly in the countries and regions where efforts to reduce hunger have stalled. Most, if not all, of the MDG targets can still be reached, but only if efforts are redoubled and refocused.
Keywords: Food supply,Cung cấp thực phẩm; Developing countries,Phát triển đất nước